Pengaruh plyometric exercise terhadap kemampuan agility pemain futsal tingkat sekolah menengah: A systematic literature review - Hagia Sofia Katleana; Riza Pahlawi (Holistik Jurnal Kesehatan, 2026)
Background: Agility is a crucial component of athletic fitness in futsal, particularly for high school players who must perform rapid and efficient changes of direction during matches. However, training programs are not always specifically designed to optimize agility development in this population. Purpose: To synthesize scientific evidence regarding the effectiveness of plyometric training in improving agility in high school futsal players. Method: This systematic literature review followed the PRISMA 2020 guidelines and utilized a structured search in PubMed, Scopus, Google Scholar, and Semantic Scholar. Study selection was based on the PICOS criteria, which focus on experimental and quasi-experimental studies examining plyometric interventions and agility outcomes. Five eligible articles were included. Data were extracted using a standardized form and analyzed descriptively. Results: Findings consistently demonstrated that plyometric training significantly improved agility performance compared to baseline or a control group. Effective programs generally lasted 4–6 weeks and were conducted 2–3 times per week. Commonly used exercises include ladder drills, zigzag runs, squat jumps, and lateral hurdle jumps, which are measured using standardized agility tests. Conclusion: Structured plyometric training is effective in improving agility in high school futsal players and supports its practical application in school-based futsal training programs.   Keywords: Agility; Futsal; Plyometric Training.